Using the Intervention Mapping Approach to Develop a Mental Health Intervention: A Case Study on Improving the Reporting Standards for Developing Psychological Interventions - van Agteren, Joep; Iasiello, Matthew; Ali, Kathina; Fassnacht, Daniel B.; Furber, Gareth; Woodyatt, Lydia; Howard, Alexis; Kyrios, Michael (Frontiers in Psychology, 2021)
Replicating or distilling information from psychological interventions reported in the scientific literature is hindered by inadequate reporting, despite the existence of various methodologies to guide study reporting and intervention development. This article provides an in-depth explanation of the scientific development process for a mental health intervention, and by doing so illustrates how intervention development methodologies can be used to improve development reporting standards of interventions. Intervention development was guided by the Intervention Mapping approach and the Theoretical Domains Framework. It relied on an extensive literature review, input from a multi-disciplinary group of stakeholders and the learnings from projects on similar psychological interventions. The developed program, called the “Be Well Plan”, focuses on self-exploration to determine key motivators, resources and challenges to improve mental health outcomes. The program contains an online assessment to build awareness about one’s mental health status. In combination with the exploration of different evidence-based mental health activities from various therapeutic backgrounds, the program teaches individuals to create a personalised mental health and wellbeing plan. The use of best-practice intervention development frameworks and evidence-based behavioural change techniques aims to ensure optimal intervention impact, while reporting on the development process provides researchers and other stakeholders with an ability to scientifically interrogate and replicate similar psychological interventions.